OPTIMIZING FREEZE DRYING CONDITIONS AND ENHANCING QUALITY OF CHEESE POWDER FLAVOURS THROUGH SURFACE AREA TO VOLUME RATIO MANIPULATION - Saqib Manzoor; Nabila Gulzar; Saima Inayat; Ehsan Ullah (Journal of Animal and Plant Sciences, 2025)
This study aims to optimize the freeze-drying conditions for cheese powder flavor production and to evaluate the effect of cheese type and surface area-to-volume ratio of cheeses on the quality characteristics of the resulting powder flavors. During the first phase, three types of cheese (Mozzarella, Cheddar, and enzyme-modified Cheese) were prepared into three geometric forms (shreds, slices, and cubes), representing different surface area-to-volume ratios. These samples were frozen at four different temperatures (−20 °C, −30 °C, −40 °C, and −50 °C), and then freeze-dried at four shelf temperatures (20 °C, 23 °C, 26 °C, and 29 °C). Moisture content was recorded at several time intervals ranging from 5 to 26 hours to identify the most efficient freeze-drying condition. In the second phase, a factorial experiment (3 × 3) was conducted to investigate the effects of cheese type (Mozzarella, Cheddar, and enzyme-modified Cheese), and surface area to volume ratio of cheeses (shreds, slices, cubes) on the quality characteristics of resulting cheese powder flavors. The experiment was laid out in a completely randomized design with three replications resulting in a total of 9 treatments. The results showed that a longer freeze-drying time reduced the moisture content due to prolonged sublimation, with enzyme-modified Cheese requiring more time due to its dense structure and enzyme activity. Higher freezing temperatures (-50°C) resulted in faster sublimation compared to lower temperatures (-20°C), as the formation of larger ice-crystals at -50 °C facilitated more efficient water loss. The drying temperature also accelerated moisture loss by increasing the kinetic energy of the water molecules. Physicochemical analyses revealed significant differences in fat, protein, moisture, pH, acidity, and ash content between the different cheeses, with enzyme-modified cheese having higher fat and moisture content but lower protein content. The surface area-to-volume ratio had a significant positive effect (p ≤ 0.05) on moisture content, bulk and tapped density, flowability, cohesiveness, solubility index, and dispersibility. Shredded cheese powders exhibited lower density and dispersibility, but higher solubility, due to their larger surface area. Enzyme-modified Cheese showed better flowability but lower cohesiveness. Mozzarella cheese showed higher hardness and gumminess due to the formation of protein networks, especially in shredded form.
Keywords: Cheese; Physicochemical properties; Surface area to volume ratio; Texture